Study of Vibronic and Born-Oppenheimer Couplings - Lin, S. H. (1974)
The purpose of this paper has been to develop a systematic approach for classifying and distinguishing the relative orders of approximation of various types of couplings like the vibronic (Herzberg-Teller) couplings and Born-Oppenheimer couplings, and for studying the importance of the anharmonicity in the quantitative calculation of the spectral intensity and electronic relaxation. It will be shown that the perturbation parameter introduced by Born and Oppenheimer in separating the electronic and nuclear motion involved in the molecular Schrödinger equation, λ = (m/M)¼, can be used for this purpose by expanding wavefunctions and energies in power series of λ.